KONSEP MASHLAHAH DALAM PEMBAGIAN AHLI WARIS PENGGANTI: Sebuah Titik Temu antara Im?m Sy?fi’? dan Kompilasi Hukum Islam - Muhammad Hasbulloh Huda (Fakultas Syariah - IAI Al-Qolam Malang, 2019)
The discussion of the division of inheritance in Islamic sharia is a dogmatic concept that has little development space, one of which is in the discussion of the concept of dzaw? al-arh?m which is not much mentioned in the Koran or al-Hadith. While the reality of cultural life encountered many problems associated with this dzaw? al-arh?m. Then of course there will be many perceptions of ijtih?diyyah related to this dzaw? al-arh?m, among them are in the opinion of Im?m Syafi'? and the Compilation of Islamic Law in force in Indonesia. Im?m Syafi'? has the concept of inheritance for dzaw? al-arh?m which can be compared to the concept of a substitute heir in article 185 KHI, although in some respects it has differences. Both have the same passion, namely to prevent harm and ensure justice and benefit.